Carvacrol and Thymol Content Affects the Antioxidant and Antibacterial Activity of Origanum compactum and Thymus zygis Essential Oils - Mounia Chroho; Youssef Rouphael; Spyridon A. Petropoulos; Latifa Bouissane (MDPI AG, 2024)
Essential oils are of great interest due to their potent pharmaceutical and biological activities. In this study, essential oils extracted from Origanum compactum and Thymus zygis originating from the Middle Atlas of Morocco were investigated. Their chemical compositions were analyzed using gas chromatography and mass spectrometry, while the assessment of the trapping power of the radical (DPPH: 1,1-diphenyl-2-picrylhydrazyl) and the reducing antioxidant potential of ferric ions (FRAP: Ferric Reducing Antioxidant Power) were performed in order to evaluate the antioxidant activity. Their antibacterial potency was tested against six bacterial strains through the disk diffusion method. The chromatography analyses of the extracted essential oils highlighted the presence of two main components, namely carvacrol at 75.70% in O. compactum and thymol at 40.67% in T. zygis. The antioxidant activity tests showed that both essential oils demonstrated a significant antioxidant activity comparable to the positive control (e.g., ascorbic acid). The antibacterial activity results showed a strong antimicrobial effect for both essential oils, compared to synthetic antibiotics. This study affirms the presence of bioactive components with interesting antioxidant and antibacterial activities in the essential oils extracted from Origanum compactum and Thymus zygis, which could find several applications in the food and pharmaceutical industries through the substitution of synthetic antioxidants and antibiotics.